2019
DOI: 10.7759/cureus.6402
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neurological Outcome Following Subaxial Cervical Spine Trauma

Abstract: Background The treatment of traumatic subaxial cervical spine injuries remains controversial. The American Spinal Injury Association (ASIA) impairment scale (AIS) is a widely-used metric to score neurological function after spinal cord injury (SCI). Here, we evaluated the outcomes of patients who underwent treatment of subaxial cervical spine injuries to identify predictors of neurologic function after injury and treatment. Methods We performed a retrospective logistic regression analysis to determine predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…and in few cases, the cause is iatrogenic where patients underwent reoperation. 13 Our study has also shown that the rate of improvement was least in ASIA grade A. This was in concordance with Vazquez et al who studied 173 traumatic cervical SCI patients and concluded that the rate of improvement was least in ASIA grade A patients, and none of them were functional.…”
Section: Discussionsupporting
confidence: 92%
“…and in few cases, the cause is iatrogenic where patients underwent reoperation. 13 Our study has also shown that the rate of improvement was least in ASIA grade A. This was in concordance with Vazquez et al who studied 173 traumatic cervical SCI patients and concluded that the rate of improvement was least in ASIA grade A patients, and none of them were functional.…”
Section: Discussionsupporting
confidence: 92%
“…Estos sistemas proveen una categorización del patrón de lesión, así como una guía para decidir si es posible optar por el tratamiento conservador o quirúrgico. 2,8,10,19 Sharif y colaboradores y Cruz y su grupo mencionan el uso de la clasificación de la asociación de osteosíntesis para la columna AO, la cual comprende tres grupos principales: a) fracturas por compresión o estallamiento; b) lesiones por distracción que comprometen el complejo ligamentario posterior; y c) fracturas con componentes rotacionales; se incluye un grupo F para lesiones facetarias, N para déficits neurológicos y M para modificadores. 6,10,19 El sistema de puntuación SLICS puede guiar el tipo de tratamiento.…”
Section: Wwwmedigraphicorgmxunclassified
“…Debido a que la estructura y función de los segmentos C1-C1 varían considerablemente de la región C2-C7, en la práctica clínica se manejan por separado para su abordaje. 1,2 Las lesiones de la columna cervical subaxial ocurren en 2.4-3.7% de los pacientes con trauma cerrado y el lugar más común que resulta afectado es de C5 a C7 en aproximadamente 50% de los casos, además es más frecuente que el trauma occipital-C2 en una razón de proporción 2:3. La presentación de mayor incidencia es la luxofractura con afección más común del segmento C5-C6, el cual está sujeto a fijación abierta en más casos en comparación con el segmento C7-T1.…”
Section: Introductionunclassified
See 1 more Smart Citation